Answer:
The formula of the geometric sequence is a[tex]_{n}[/tex] = [tex](-3)^{n-1}[/tex]
Step-by-step explanation:
The terms of the sequence are 1, -3, 9, -27
∵ -3 ÷ 1 = -3
∵ 9 ÷ -3 = -3
∵ -27 ÷ 9 = -3
∴ There is a common ratio between each two consecutive terms
∴ The sequence is geometric
∵ The formula of the geometric sequence is a[tex]_{n}[/tex] = a [tex]r^{n-1}[/tex], where
∵ The first term is 1
∴ a = 1
∵ The common ratio is -3
∴ r = -3
→ Substitute them in the formula above
∵ a[tex]_{n}[/tex] = (1) [tex](-3)^{n-1}[/tex]
∴ a[tex]_{n}[/tex] = [tex](-3)^{n-1}[/tex]
∴ The formula of the geometric sequence is a[tex]_{n}[/tex] = [tex](-3)^{n-1}[/tex]